Learning to write book reviews for publication: A collaborative action research study on student-teachers' perceptions, motivation, and self-efficacy. (December 2020) - Banegas, Darío Luis; Loutayf, María Soledad; Company, Susana; Alemán, María José; Roberts, Grisel
Abstract: The purpose of this collaborative action research-based study was to explore the effects of learning to write book reviews for publication on 57 student-teachers' experience with academic writing in initial English language teacher education (IELTE) in Argentina. The initiative was embedded in four different modules at three institutions. Data were gathered from March to November 2018 through an online questionnaire and group interviews. Descriptive statistics and thematic analysis of the data collected show that writing book reviews for publication improved student-teachers' motivation, sense of self-efficacy, and overall perception of academic writing given the authenticity of audience embedded in the writing tasks. The findings confirm that learning to write for publication, when based on genre pedagogy, helps student-teachers develop professionally through experiential learning and therefore teacher educators may need to consider embedding similar initiatives in IELTE. Unlike previous studies, peer collaboration did not have a positive effect on the student-teachers' writing development. Pedagogical and research implications are included. Highlights: Learning to write book reviews is meaningful with undergraduate student-teachers. Learning to write for publication influences student-teachers' motivation. Learning to write for publication improves self-efficacy and academic writing. Authenticity of audience should be an essential feature of writing tasks. Peer collaboration may not always yield positive results.